Model for improved undergraduate training in translational conservation science. Issue 1 (12th April 2019) - Kelley, Patricia H.; Dietl, Gregory P.; Visaggi, Christy C.
Abstract : The "Research Experiences for Undergraduates (REU) in Biodiversity Conservation" project models transdisciplinary training in conservation science, and particularly in the emerging field of conservation paleobiology (CPB), which applies geohistorical records (e.g., sediments, fossils) and approaches to solve conservation problems. We analyzed recent funding patterns in the National Science Foundation REU program (Biological Sciences and Geosciences directorates) and found that, at most REU sites, undergraduates conduct individual projects supervised by a mentor. In contrast, at the REU in Biodiversity Conservation Site, students from geology, biology, archaeology, and environmental sciences worked in transdisciplinary teams on conservation‐related research using fossil, archaeological, and modern samples. The project successfully incorporated CPB approaches and taught research and soft skills useful in conservation; 85% of students subsequently pursued STEM graduate study or employment. However, because translational science partnerships with conservation practitioners were not sought, the research‐implementation gap remained. We propose a new model for REU sites involving conservation practitioners and stakeholders as partners in research that includes the human dimension and meets community needs, resulting in transdisciplinary, team‐focused training that yields actionable results. We recommend that the National Science Foundation encourage researchers to think beyond typical one‐on‐one mentorship when planning an REU, especially for conservation science projects.